The influence of parenting styles on parental political orientation and voting behavior of young adult - Omar, Muhamad Fuzi; Abdul Manaf, Siti Noratikah; Othman, Muhammad Hanif (Globeedu Group, 2014)

(untitled)
The main purposes of the study are to examine the relationship between parenting styles and parental political orientation and to find out whether voting behavior of young adults is associated with parenting practices. 39 items on parenting styles, parental political orientation & voting behavior were completed by 239 respondents. The data was collected using a structured questionnaire. Approximately, 300 sets of questionnaires were distributed among students and approximately 239 questionnaires were collected back and returned from respondents progressively. This study used descriptive, factor analysis, and cluster analysis. Furthermore, the data was also verified using Mann-Whitney and multiple regression analysis to test predictability of independent variables. The results show that there are four parenting practices among parents of IIUM students which are consistent with Baumrind’s authoritarian, authoritative, permissive and neglectful typologies. In addition, the study indicates that authoritarian parents have proactive involvement in knowledge transmission of politics to their offspring. On the other hand, surprisingly in the latter test reveals that high representation of young adults in election is positively associated with authoritative parenting. Despite the fact that authoritarian parents are identified as the active agent in political socialization, authoritative parents however, scored positive behavior to young adults’ attitudes in voting. Evaluating the issues of falling level of electoral participation among young adults, this research looks into the possible reasons that contribute to young adult’s turning out and not turning out for election. Keywords: Political Orientation, 4 Parenting Styles; Authoritarian, Authoritative and Neglectful, Permissive and Voting Behavior